Qualitative assessment of sex-stratified human papillomavirus transmission dynamics in South Korea - Soyoung Kim; Olive R. Cawiding; Aurelio A. de los Reyes V; Sunhwa Choi (BMC Public Health)
Abstract Background Human papillomavirus (HPV) vaccination, primarily targeting females aged 9–14 years, is pivotal in preventing HPV infections. This case study evaluates the effects of HPV vaccination in South Korea within the primary target group using incidence data and proposes optimal intervention strategies for maximizing the effectiveness of HPV mitigation programs. Methods We developed a mathematical model to simulate HPV transmission dynamics in South Korea, incorporating sex-stratified groups. We assessed vaccination rates before and after HPV inclusion in the National Immunization Program (NIP). Using the optimal control theory, we identified effective strategies involving HPV treatment and vaccination for females and males and analyzed their implementation costs and effectiveness. Results The inclusion of female HPV vaccination in the NIP increased the transmission rate from females to males, increasing HPV prevalence among males. As a standalone intervention, treatment is more cost effective and can minimize HPV infections by 2030. In dual control strategies, simultaneously treating both sexes is more effective in reducing infections and improving the average cost effectiveness ratio (ACER) compared to vaccination alone. Targeting males exclusively could potentially achieve greater reductions than targeting females. In triple strategies, combining treatment interventions for both sexes with either male or female vaccination achieves a lower ACER and higher reductions in HPV infections. Overall, implementing a combined (quadruple) strategy is projected to reduce infections by approximately 266,000 in 2030. Simultaneous implementation of controls significantly reduces the burden on vaccination control and treatment duration. Conclusion Treatment control provides an immediate reduction in HPV infections but requires consistent implementation. Increasing vaccination rates by expanding the target population enlarges the protected group. Although vaccination control may not yield rapid reductions compared to treatment, it demonstrates more sustained effects. Combining intervention strategies reduces the cost for each measure and significantly increases the total infections averted. These results can aid public health decision-making in South Korea and guide HPV prevention strategies in other countries.